Analysis of The Effect of Work Motivation, Job Satisfaction, and Work Discipline on Employee Performance at PT Bank Artha Graha - Sri Lestari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Employee performance is a critical factor in determining organizational success, particularly in the banking industry, which requires high service quality and operational efficiency. This study aims to analyze the effects of work motivation, job satisfaction, and work discipline on employee performance at PT Bank Artha Graha Branch Lampung. This research adopts a quantitative approach using primary data collected through questionnaires distributed to 91 employees of PT Bank Artha Graha Branch Lampung. The data were analyzed using multiple linear regression analysis with the assistance of SPSS. Prior to hypothesis testing, validity and reliability tests were conducted, along with classical assumption tests, including normality, multicollinearity, and heteroskedasticity tests, to ensure the suitability of the regression model. The results indicate that work motivation, job satisfaction, and work discipline each have a positive and significant effect on employee performance. Among these variables, work discipline is identified as the most dominant factor influencing performance. Simultaneously, the three independent variables significantly affect employee performance, indicating that employee performance is influenced by a combination of motivational, psychological, and behavioral factors. The coefficient of determination shows that work motivation, job satisfaction, and work discipline explain 47.2% of the variation in employee performance, while the remaining 52.8% is explained by other factors not examined in this study. These findings imply that management should prioritize efforts to enhance employee motivation, maintain job satisfaction, and consistently enforce work discipline to improve performance. This study contributes to the empirical literature on human resource management in the banking sector and provides practical insights for improving organizational performance.